A Standard Criteria for Assesing the Health of Coral Reefs: Implication for Management and Conservation - Zamani, Neviaty P.; Madduppa, Hawis H (Journal of Indonesian Coral Reefs, 2011)
Coral reefs ecosystems are currently under high threat from human activities. LIPI (Indonesian Institute of Sciences) reported that only 5.2 % in 2006 of Indonesian coral reef (an area of 85.700 km2) is still considered in very good. Although these data are further need to be verified, but this can be as basic information that coral reefs in Indonesia need special attention and action. It is unfortunate that the current method to determine the health of reefs is limited. General practitioners are usually using a standard categorization by Yap and Gomez (1988). However, many drawbacks appeared of the use of this standard in Indonesia. This study aims to explore and evaluate the various standards in determining the health of coral reef, and formulate an easy and precise standard for practitioners. This study combines several standards of key parameters in coral reefs. The parameter that used in determining the health of reefs in this study is a combination of percent cover of live coral, algae and mortality index. The proposed criteria for health of coral reef as follows: excellent, good, fair, and poor. These criteria are expected to facilitate practitioner in evaluating the health of coral reefs in accurate and precise that is suitable for Indonesian coral reefs.